Avaliação de fatores prognósticos e tratamento quimioterápico adjuvante em neoplasias mamárias malignas felinas - Cecília Bonolo de Campos (2013)
Mammary neoplasms are the third most frequent tumor in felines. Median overall survival is considered as less than one year and prognosis is guarded to poor. Surgery is the main treatment option for feline mammary neoplasms. Additional clinical studies are necessary in order to evaluate more efficient chemotherapy protocols that may increase overall survival (OS). Furthermore, the understanding of prognostic and predictive factors associated to the biological behavior of neoplastic diseases enables individualized therapeutic strategies aiming towards an increase in disease free interval and overall survival (OS). Therefore, the aim of this study was to evaluate the surgical therapeutic strategy associated or not to chemotherapy with carboplatin, comparing both treatments through OS; investigate the association of prognostic factors suggested by the literature for feline mammary neoplasms, associating data to OS; in addition, to describe, for the first time in the feline species, histopathological, immunohistochemical, and clinical of a malignant adenomyoepithelioma (MA) and glycogenrich clear cell carcinoma (GRCCC). For the therapeutic evaluation, 16 queens were studied, divided into a group only treated with surgery and another treated with surgery associated to carboplatin. For the evaluation of prognostic factors, 37 queens diagnosed with malignant mammary neoplasms were evaluated. Clinical staging, histological type and grade, and immunohistochemical profile for Ki-67, ER, PR, Her-2, Cox-2, and VEGF were correlated to OS findings. No statistical significant difference in OS was observed when comparing the different treatments (p=0.883). Regarding the prognostic factors, 35% presented metastasis; the majority was classified as stage III, tubulopapillary carcinomas and grade II. Mammary carcinomas positive for hormonal receptors, negative for Her-2, and with superexpression of VEGF prevailed. Immunolabeling for Ki-67 (p=0.046) and Cox-2 (p=0.007) were higher in metastases than in primary tumors. Protein expression of Cox-2 (p=0.089), Her-2 (p=0.012) and histological grade (p=0.080) were correlated to OS. Diagnosis was confirmed through PAS staining for GRCCC and immunohistochemical analysis of p63 for the MA. Both neoplasms presented aggressive biological behavior, characterized by lymph node metastasis. Results suggest that the therapeutic benefit of carboplatin remains invalidated for feline mammary carcinomas, and that the inhibition of ovarian hormones and Cox-2 may possibly represent a therapeutic option. Furthermore, Cox-2 and Ki-67 should be evaluated in primary tumors and lymph nodes, and that histological grade, Her-2, and Cox-2 directly influence in OS.